Songs in the Teaching of Listening for Elementary School Students - Sitti Hadijah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2019)
Lack of motivation among students may cause teachers to be less successful in teaching a foreign language. To help the students to be motivated in listening, the teacher should find an appropriate technique to apply in teaching listening. Generally, the children like listening to song because they like something cheerful. If they feel happy, they will do it over and over again. If the students enjoy listen to the songs, they will enjoy learning listening by using the song, too. Promoting the students to love learning English will motivate to study. Songs are authentic materials and can make the students fun. Songs as media are very useful to help students improve their motivation. By enhancing the students’ motivation, the English teachers have a chance to enhance the students’ listening achievement by using the songs in the classroom learning.